2018
DOI: 10.1021/acs.langmuir.8b03454
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation-Mediated, Zwitterionic Polydopamine Coatings for Marine Antifouling Applications

Abstract: We synthesized a zwitterionic dopamine derivative (ZW-DOPA) containing both catechol and amine groups, and we demonstrated an excellent marine antifouling surface by controlling the oxidation of ZW-DOPA. The oxidation was mediated by the deprotonation of catechol or the addition of an oxidant (ammonium persulfate (AP) or sodium periodate (NaIO4)). The oxidation and subsequent molecular transformation of ZW-DOPA was investigated over time by UV–vis spectroscopy. Among the different oxidation conditions tested, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 51 publications
0
68
0
Order By: Relevance
“…[102a] A disulfide containing ester of dopa was used to obtain a polymer by air oxidation, which is cleavable by reduction (Scheme ). [102b] Short interaction of sodium periodate with some side‐chain substituted dopamines was reported to stop at orange colored quinone monomers without providing comprehensive spectroscopic evidence except UV‐spectroscopy (Scheme ). Their rearrangement to 5,6‐dihydroxyindoles mediated by macrophage migration inhibitor factor (MIF) was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[102a] A disulfide containing ester of dopa was used to obtain a polymer by air oxidation, which is cleavable by reduction (Scheme ). [102b] Short interaction of sodium periodate with some side‐chain substituted dopamines was reported to stop at orange colored quinone monomers without providing comprehensive spectroscopic evidence except UV‐spectroscopy (Scheme ). Their rearrangement to 5,6‐dihydroxyindoles mediated by macrophage migration inhibitor factor (MIF) was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative polymerization of a zwitterionic dopa ester[102a] (top), of a dopa ester disulfide (left middle),[102b] formation of 5,6‐dihydroxyindoles by NaIO 4 oxidation of side‐chain substituted DA under controlled conditions (bottom). [102b]…”
Section: Resultsmentioning
confidence: 99%
“…The number of used monomers to synthesis polyzwitterions is rather limited focusing on phosphobetaine, carboxybetaines, 2‐methacryloyloxyethyl phosphorylcholine, and sulfobetaines. However, alternative monomers such as serine methacrylate and ornithine methacrylamide to obtain amino‐acid‐based zwitterionic polymers, or a zwitterionic dopamine derivative started to emerge. Zwitterionic materials are essential for life illustrated by specific phospholipids or osmolytes, inspiring scientists in material design.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the ion-dipole interactions between zwitterions and water molecules, hydration layers are formed on the zwitterionic-polymer-coated surfaces, preventing marine fouling. [22][23][24] Zhang et al reported that coating glass surfaces with poly(sulfobetaine methacrylate) makes them superhydrophilic. 24 Notably, these polymer-coated glass surfaces exhibited an excellent marine antifouling ability, preventing marine diatoms from adhering to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…The same principle for inhibiting marine fouling was also implemented using zwitterionic polymers. Because of the ion–dipole interactions between zwitterions and water molecules, hydration layers are formed on the zwitterionic‐polymer‐coated surfaces, preventing marine fouling 22–24 . Zhang et al .…”
Section: Introductionmentioning
confidence: 99%